Investigation of the response to the enterobacterial common antigen after typhoid vaccination - Milhomem,Arlete M. (1987)
Antibodies against the Salmonella typhi enterobacterial common antigen (ECA) and the O and H antigens were investigated in sera from healthy male subjects who had been previously vaccinated with the typhoid vaccine. No serological response to ECA was observed. Sera from subjects not previously vaccinated presented titers of ECA hemagglutinins which quantitatively were related to the presence ofH titers, but not to O agglutinins but with no statistical significance. The results are discussed in relation to the possible protective immunological mechanisms in typhoid fever.